Dapagliflozin versus sacubitril–valsartan for heart failure with mildly reduced or preserved ejection fraction - Arbel, Ronen; Azab, Abed N.; Oberoi, Mansi; Aboalhasan, Enis; Star, Artyom; Elhaj, Khaled; Khalil, Fouad; Alnsasra, Hilmi (Frontiers in Pharmacology, 2024)
Background and Aim: Heart failure with preserved ejection fraction (HFpEF) is associated with an increased risk of heart failure (HF) hospitalizations and cardiovascular death (CVD). Both dapagliflozin and sacubitril-valsartan have recently shown convincing reduction in the combined risk of CVD and HF hospitalizations in patients with mildly reduced ejection fraction (HFmrEF) or HFpEF. We aimed to investigate the cost-per-outcome implications of dapagliflozin vs. sacubitrilvalsartan in the treatment of HFmrEF or HFpEF patients.Methods: We compared the annualized Cost Needed to Treat (CNT) to prevent the composite outcome of total HF hospitalizations and CVD with dapagliflozin or sacubitril-valsartan. The CNT was estimated by multiplying the annualized Number Needed-to-Treat (aNNT) by the annual cost of therapy. The aNNT was calculated based on data from the DELIVER trial for dapagliflozin, and pooled analysis of PARAGLIDE-HF and PARAGON-HF trials for sacubitril-valsartan. Costs were based on 2022 US prices. Scenario analyses were performed to attenuate the differences in the studies' populations.The aNNT with dapagliflozin in DELIVER was 30 (95% confidence interval [CI]: 21-62) versus 44 (95% CI: 25-311